Health at older ages : the causes and consequences of declining disability among the elderly - Cutler, David M.; Wise, David A. (Chicago : University of Chicago Press, 2008)
Americans are living longer--and staying healthier longer--than ever before. Despite the rapid disappearance of pensions and health care benefits for retirees, older people are healthier and better off than they were twenty years ago. In Health at Older Ages, a distinguished team of economists analyzes the foundations of disability decline, quantifies this phenomenon in economic terms, and proposes what might be done to accelerate future improvements in the health of our most elderly populations. This breakthrough volume argues that educational attainment, high socioeconomic status, an older ret.
Disability risk and the value of disability insurance / Amitabh Chandra and Andrew A. Samwick -- Why are the disability rolls skyrocketing? The contribution of population characteristics, economic conditions, and program generosity / Mark Duggan and Scott A. Imberman -- Early retirement and DI/SSI applications: exploring the impact of depression / Rena M. Conti, Ernst R. Berndt, and Richard G. Frank -- Trends in assistance with daily activities: racial/ethnic and socioeconomic disparities persist in the U.S. older population / Vicki A. Freedman [and others] -- How do Medicare beneficiaries with physical and sensory disabilities feel about their health care? / Lisa I. Iezzoni, Jane R. Soukup, and Suzanne G. Leveille -- Inter-spousal mortality effects: caregiver burden across the spectrum of disabling disease / Nicholas A. Christakis and Paul D. Allison.
"This volume consists of papers presented at a conference held in Jackson Hole, Wyoming, in October 2004"--Page xi
Includes bibliographical references and indexes.
Print version record.
eBooks on EBSCOhost
Keywords: Older people -- Health and hygiene -- United States -- Statistics; Older people with disabilities -- United States -- Statistics; Older people; People with disabilities; Aged; Geriatric Assessment; Chronic Disease -- economics; Chronic Disease -- prevention & control; Persons with Disabilities; Health Services for the Aged -- trends; United States; Personnes âgées -- Santé et hygiène -- États-Unis -- Statistiques; Personnes âgées handicapées -- États-Unis -- Statistiques; Personnes âgées.; Personnes handicapées.; elderly; MEDICAL -- Geriatrics; MEDICAL -- Nursing -- Gerontology; People with disabilities; Older people; Older people -- Health and hygiene; Older people with disabilities; United States; Statistics